2020
DOI: 10.3389/fpsyt.2019.00999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Depression, Anxiety, Cognitive Control, Craving, Physical Fitness and Quality of Life in Methamphetamine-Dependent Patients

Abstract: Methamphetamine (MA) abuse results in a variety of harmful changes in mood states and cognitive function, together with declined physical health and quality of life. Recent studies highlighted the therapeutic potential of physical exercise on MA addiction. Physical exercise improves emotional state and general health conditions, enhances cognitive function, reduces relapse rate, and facilitates abstinence, thereby improves the overall quality of life of the drug users. This review summarizes the present situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 72 publications
2
37
0
1
Order By: Relevance
“…The association between alcohol craving and quality of life was previously studied by Herrold et al in war veterans demonstrating that high levels of craving were associated with poor perceived quality of life, bothmentally and physically (39). At the same time, improving the quality of life, for instance, through physical exercise, can play an important role in reducing craving and, therefore, conducts of abuse (40). Several studies have demonstrated that stress, negative mood, and craving could expose addicted patients to relapse and dropout from treatment (41).…”
Section: Discussionmentioning
confidence: 92%
“…The association between alcohol craving and quality of life was previously studied by Herrold et al in war veterans demonstrating that high levels of craving were associated with poor perceived quality of life, bothmentally and physically (39). At the same time, improving the quality of life, for instance, through physical exercise, can play an important role in reducing craving and, therefore, conducts of abuse (40). Several studies have demonstrated that stress, negative mood, and craving could expose addicted patients to relapse and dropout from treatment (41).…”
Section: Discussionmentioning
confidence: 92%
“…Exercise can improve METH-dependent emotional state, cognitive control, and cravings [34]. Herein, eight weeks of aerobic combined with resistance exercise significantly reduced the anxiety and depression symptoms of METH withdrawal [35].…”
Section: The Effect Of Exercise On 5-ht Vas Craving Vas Control Impulsementioning
confidence: 86%
“…As one of the most commonly abused psychostimulants in the world (Siefried et al, 2020), methamphetamine (METH) abuse results in various severe complications systemically affecting multiple organs, especially the brain (Casaletto et al, 2015;Huang et al, 2019). METH addiction can induce neurodegenerative changes in the hippocampus and frontal cortex, which are all related to long-term cognitive dysfunction and memory deficits in humans (Casaletto et al, 2015;Chen et al, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%